Synergy of the National Sharia Board and the Financial Services Authority in the Development of Sharia Financial Regulations in Indonesia - Ermaini, Ermaini; Arniwita, Arniwita; Putra, Iwan Eka; Ridwan, Mohammad; Munzir, Munzir; Sudarmanto, Eko (Westscience Press, 2025)
This study examines the synergy between the National Sharia Board (Dewan Syariah Nasional, DSN) and the Financial Services Authority (Otoritas Jasa Keuangan, OJK) in developing sharia financial regulations in Indonesia. Employing a qualitative research approach, the study focuses on data obtained from semi-structured interviews with three informants, comprising a DSN representative, an OJK official, and a sharia finance expert. Key findings reveal the importance of collaborative decision-making, role clarity, structured communication mechanisms, and capacity building in ensuring effective regulation. However, challenges such as delays in policy integration and difficulties in addressing financial technology innovations persist. This research highlights the critical role of synergy between religious and regulatory institutions in fostering the growth of the sharia finance sector, positioning Indonesia as a global leader in Islamic finance.